RELIGIOUS TELEVISION PROGRAM "DNES"(NOWADAYS) AS SOURCE OF THE FORMATION OF SPIRITUAL VALUES OF YOUTH - Dymnich, N. D. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
In the article the religious television program “ Dnes”(Nowadays) has been analised through the prism of its impact on the formation of spiritual values of youth. Attention is focused on the specifics of the sermon as a genre of television.